Diatoms dominate the eukaryotic metatranscriptome during spring in coastal 'dead zone' sediments. Issue 1864 (4th October 2017) - Broman, Elias; Sachpazidou, Varvara; Dopson, Mark; Hylander, Samuel
Abstract : An important characteristic of marine sediments is the oxygen concentration that affects many central metabolic processes. There has been a widespread increase in hypoxia in coastal systems (referred to as 'dead zones') mainly caused by eutrophication. Hence, it is central to understand the metabolism and ecology of eukaryotic life in sediments during changing oxygen conditions. Therefore, we sampled coastal 'dead zone' Baltic Sea sediment during autumn and spring, and analysed the eukaryotic metatranscriptome from field samples and after incubation in the dark under oxic or anoxic conditions. Bacillariophyta (diatoms) dominated the eukaryotic metatranscriptome in spring and were also abundant during autumn. A large fraction of the diatom RNA reads was associated with the photosystems suggesting a constitutive expression in darkness. Microscope observation showed intact diatom cells and these would, if hatched, represent a significant part of the pelagic phytoplankton biomass. Oxygenation did not significantly change the relative proportion of diatoms nor resulted in any major shifts in metabolic 'signatures'. By contrast, diatoms rapidly responded when exposed to light suggesting that light is limiting diatom development in hypoxic sediments. Hence, it is suggested that diatoms in hypoxic sediments are on 'standby' to exploit the environment if they reach suitable habitats.